Portrait of Religious Moderation by South Kalimantan Netizens on Da’wah Account KH. Ilham Humaidi @khodimukum_humaed - Armiah, Armiah; Hasanah, Risqiatul; Falikhah, Nur (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
This research aims to determine the interaction, meaning of the text and cultural context of netizens in understanding moderation content on KH.Ilham Humaidi's Instagram account is a da'wah strategy in the digital era. The hope is that there will be an openness to national insight that will strengthen national integration, especially in Kalimantan. Researchers used cyber media analysis by collecting data online on the account @khodimukum_humaed. This research shows that Instagram @khodimukum_humaed has become a media that holds religious communities together. Netizens often use cultural artefacts, language and two-way communication models. In digital culture, there is interaction through reposting, liking, commenting, mentioning, and direct messaging followers. Through his account, Guru Ilham Humaidi wishes to provide a more moderate understanding of Islam by Ahlus Sunnah wal Jama'ah, in addition to daily practice, worship and fiqh as a da'wah strategy in the digital era in realizing Islam rahmatan lil alamin.